2012
DOI: 10.1089/ees.2010.0487
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Ecological Factors on Anaerobic Ammonia-Oxidizing Bacteria Enrichments

Abstract: Anaerobic ammonia-oxidizing bacteria (AnAOB) have remarkably strong ability of coupling ammonia and nitrite into nitrogen gas and have been regarded as one of the most promising techniques for wastewater nitrogen removal. However, these anaerobic autotrophs are vulnerable to some environmental factors such as dissolved oxygen (DO), organic carbon, or antibiotics, which are inevitable in actual sewage or industrial wastewater. From an ecological perspective, the factors may not directly inhibit AnAOB but stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Many studies have shown that successful cultivation of anammox bacteria from conventional sludge takes long time; i.e., generally from 4 months to 1 year [24]. Such time will be influenced by factors like (i) the ecological characteristics of the seeding sludge including initial concentration and relative abundance of anammox bacteria [24], (ii) effective biomass retention inside the reactor [25], and (iii) the environmental conditions applied: temperature, pH, and concentration of NH 4 + , NO 2 -, dissolved oxygen (DO), organic carbon, sulphide and other inhibitors like metals and antibiotics [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that successful cultivation of anammox bacteria from conventional sludge takes long time; i.e., generally from 4 months to 1 year [24]. Such time will be influenced by factors like (i) the ecological characteristics of the seeding sludge including initial concentration and relative abundance of anammox bacteria [24], (ii) effective biomass retention inside the reactor [25], and (iii) the environmental conditions applied: temperature, pH, and concentration of NH 4 + , NO 2 -, dissolved oxygen (DO), organic carbon, sulphide and other inhibitors like metals and antibiotics [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The enrichment process often takes a long time, months or even years, to succeed (Sun et al, 2011). Enrichment time can be influenced by several factors, including ecological characteristics of the seeding sludge (Tao et al, 2013), biomass retention inside the reactor (Fux & Siegrist, 2004), and the environmental conditions applied, such as: temperature, pH, and concentrations of NH4+, NO2, dissolved oxygen (DO), organic carbon, sulfide, and other inhibitors (Carvajal‐Arroyo et al, 2013; Jin et al, 2012; Tao & Gao, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, such one-stage system is not stable because of many reasons such as variations in DO, temperature or the inhibitors from the influents (Tao and Gao, 2012) and amongst them, the temperature is an important factor . Besides of the impact on AOB-AnAOB biofilms/granules, temperature can also affect an AD process.…”
Section: Introductionmentioning
confidence: 99%